Stone vessels in the Near East during the Iron Age and the Persian period (c. 1200-330 BCE) - Squitieri, Andrea, (Archaeopress ancient Near Eastern archaeology ;, 2017)
This text focuses on the characteristics and the development of the stone vessel industry in the Near East during the Iron Age and the Persian period (c. 1200 - 330 BCE). Three main aspects of this industry are investigated. First, the technology behind the manufacture of stone vessels, the tools and techniques, and how these changed across time. Second, the mechanisms of exchange of stone vessels and how these were affected by the changing political landscape through time. Third, the consumption patterns of stone vessels in both elite and non-elite contexts, and how these patterns changed through time.